Using Microsoft Teams and Outlook Together: Maximizing Productivity (2020). - von Courter, Gini (linkedin.com, 2020)
Explore the tools provided by Microsoft Outlook and Teams and discover how to use the programs together to increase collaboration and maximize productivity.